Expansion of Oil Palm Plantations: PT Agrapana Wukir Panca Social, Economic and Environmental Issues (Case Study of Pelalawan District, Riau) - Ardiana Suryaningsih; Dian Kristanti; Taufiq Bimo Nugroho (Syntax Corporation Indonesia, 2023)
Oil palm plantations have positive and negative impacts on the environmental, social and economic aspects of local communities. Through an understanding of the data on environmental, social and economic conditions makes it easier for decision makers in policy. This research uses survey methods and in-depth interviews (state the number of respondents, state in-depth interviews). This study aims to measure the level of economic, social and ecological vulnerability due to oil palm plantations. The data used are primary data and secondary data. Primary data collection through structured and in-depth observation and interviews. Secondary data is obtained from the village office, related government agencies, BPS, books, journals, or data from the internet which contains theories or related research results. The results of this study explain that oil palm expansion that occurs in Terantang Manuk Village is through the PIR-Trans pattern, KKPA, PKS without plantation, buying and selling, grants, and self-help or independent. The environmental impact caused by oil palm expansion is reducing fruit, fish, vegetable and game shellfish and decreasing the quantity of groundwater, especially during the dry season. The economic impact due to the expansion of oil palm plantations has seen an increasingly unified economy between the upper, middle and lower classes. Meanwhile, the resulting social impact is the change in customary norms, the practice of leasing and new conflicts.